PRAKTEK JUAL BELI PRODUK MAKANAN TANPA LABEL HALAL MENURUT HUKUM ISLAM - Irwandi Irwandi; Hendra Setiawan (AL-ILMU, 2022)
Muslims in consuming food and drinks are bound by the teachings of Islam which requires the fulfillment of food requirements for consumption, namely the food must be halal and good. The basis used to show the necessity of consuming food and drink, plants and animals/animals that have been halal and good. What is the view of Islamic law on the practice of buying and selling food products without a halal label, What is the responsibility of entrepreneurs producing food without a halal label in the city of Sabang, what are the legal consequences for entrepreneurs producing food without a halal label. This study aims to find out, to find out and explain the law of buying and selling food products without halal labels according to Islamic law, to find out and explain the responsibilities of food production entrepreneurs without halal labels in the city of Sabang, to find out the legal consequences received by food production entrepreneurs without halal labels. according to Islamic law and Positive Law. In writing this thesis, the author uses the method of field research (field research), namely research conducted directly in order to obtain data that is closely related to research by interviewing respondents and informants. The practice of buying and selling food products without halal labels is very popular with the public, considering that these food products are considered natural, in Islamic law buying and selling as above is legal or permissible. as long as no prohibited compositions or other deviations are found by the Manufacturer. However, if found substances that are harmful to the health of consumers or compositions that are forbidden to be consumed by Islamic consumers, then it is Haram. Duties and Rights of Food processing business actors, continue to use halal food, but it is not clean, sterile, hygienic, and not good for consumption because some use hazardous materials. However, using the halal label will affect consumer interest in consuming their merchandise. So that it makes consumers safe and comfortable in consuming it. Legal consequences for food business actors can be in the form of administrative sanctions, namely, fines, revocation of business licenses, compensation. Meanwhile, in criminal terms, business actors can be punished with a maximum of 5 years and a fine of 2 billion. It is recommended to LPPOM-MUI and BPOM to be more careful and critical in examining the composition and tools used to make and produce packaged food in accordance with Islamic teachings. It is hoped that LPPOM-MUI and BPOM as well as the government will take firm action against business actors who produce packaged food without halal certification and halal labels. As well as facilitating the management of halal certificates for free. It is expected that producers who produce packaged, ready-to-eat food are required to include a halal label on packaged food products to provide protection to Muslim consumers as well as being Halal and good for consumption.